1998
DOI: 10.1074/jbc.273.4.2416
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Eukaryotic Translation Initiation Factor 2 Mediates Apoptosis in Response to Activation of the Double-stranded RNA-dependent Protein Kinase

Abstract: The interferon-inducible, double-stranded (ds) RNAdependent serine/threonine protein kinase (PKR) plays a role in viral pathogenesis, cell growth, and differentiation and is implicated as a tumor suppressor gene. Expression of a trans-dominant negative, catalytically inactive mutant PKR protected NIH3T3 cells from apoptosis in response to either treatment with tumor necrosis factor ␣ (TNF␣), serum deprivation. In cells expressing mutant PKR, TNF␣, but not dsRNA induced transcription from a nuclear factor B-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
322
5
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(346 citation statements)
references
References 68 publications
14
322
5
2
Order By: Relevance
“…However, the degree of inhibition was larger than that observed in cells treated with rapamycin indicating that additional e ects contribute to the shut-o of protein synthesis in cells su ering DNA damage. It has been suggested that phosphorylation of eIF2a may be important during virus-induced apoptosis (Jagus et al, 1999;Srivastava et al, 1998). Apoptosis can be triggered by the interferon-induced protein kinase PKR that phosphorylates eIF2a and thus inhibits protein synthesis at the level of initiation (Balachandran et al, 1998;Donze et al, 1999;Gil et al, 1999;Takizawa et al, 1999;Yeung et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the degree of inhibition was larger than that observed in cells treated with rapamycin indicating that additional e ects contribute to the shut-o of protein synthesis in cells su ering DNA damage. It has been suggested that phosphorylation of eIF2a may be important during virus-induced apoptosis (Jagus et al, 1999;Srivastava et al, 1998). Apoptosis can be triggered by the interferon-induced protein kinase PKR that phosphorylates eIF2a and thus inhibits protein synthesis at the level of initiation (Balachandran et al, 1998;Donze et al, 1999;Gil et al, 1999;Takizawa et al, 1999;Yeung et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the 4 h DMSO control sample was set at 100%. (*=P50.05, **=P50.005 versus appropriate DMSO control) implicated in apoptosis (Srivastava et al, 1998;Jagus et al, 1999;Clemens, 1996). To ascertain whether etoposide a ected the phosphorylation of eIF2a we used isoelectric focusing followed by immunoblotting to assess the proportion of eIF2a which was in its phosphorylated form at each time.…”
Section: Effect Of Etoposide On Other Proteins That Regulate Translationmentioning
confidence: 99%
“…They are also more resistant to serum deprivation and have altered cell cycle characteristics (Zamanian-Daryoush et al, 1999). TNF at relatively high concentrations can induce apoptosis in cultured cells by a mechanism that involves eIF-2a phosphorylation (Srivastava et al, 1998). The connection between protein synthesis inhibition resulting from eIF-2a phosphorylation and apoptosis is not clear but overexpression of Ser-51-Ala mutant eIF-2a that is resistant to phosphorylation protects cells from TNFinduced (and serum induced) apoptosis (Srivastava et al, 1998).…”
Section: Signaling Via Pkrmentioning
confidence: 99%
“…TNF at relatively high concentrations can induce apoptosis in cultured cells by a mechanism that involves eIF-2a phosphorylation (Srivastava et al, 1998). The connection between protein synthesis inhibition resulting from eIF-2a phosphorylation and apoptosis is not clear but overexpression of Ser-51-Ala mutant eIF-2a that is resistant to phosphorylation protects cells from TNFinduced (and serum induced) apoptosis (Srivastava et al, 1998). The link between the TNF signaling pathway and PKR activation also remains to be determined.…”
Section: Signaling Via Pkrmentioning
confidence: 99%
“…In mammalian cells, the assembly of SGs is initiated by the phosphorylation of eIF2␣ (Kedersha et al, 1999), a translation initiation factor that loads the initiator tRNA onto the small ribosomal subunit (reviewed by Berlanga et al, 1998;Gray and Wickens, 1998). Phosphorylation of eIF2␣ inhibits protein translation and promotes the accumulation of untranslated mRNA (Farrell et al, 1977;Srivastava et al, 1998). The related RNA-binding proteins TIA-1 and TIAR act downstream of the phosphorylation of eIF2␣ to recruit these untranslated mRNAs to SGs (Kedersha et al, 1999).…”
Section: Introductionmentioning
confidence: 99%